(untitled) (Research, Society and Development, 2020)
Ethics analyzes the moral problems that affect the well-being and quality of life of humans and non-humans and their environments. To this end, it seeks to reflect on values and guiding principles of human life and professional practices. The present work aimed to understand the process of ethical training of psychology students at a public college in the state of Rio de Janeiro. To this propose, we conducted individual interviews, with a semi-structured script, with thirty students completing the Psychology course (from the eighth to the eleventh period). We analyzed the data according to Bardin’s content analysis proposal. Most of the interviewees considered that to be ethical in the professional practice means “to respect the other”. The most recurrent response explaining the values that the interviewees consider essential for their professional activity was “listening / welcoming attitude without prior judgments”. Finally, we argue that ethical training should permeate the academic and professional training of the psychology student, preferably also in a transversal way, and be promoting the debate between teachers, students and society.